Pemberdayaan Womenpreneur Pucang: Modal Sosial dan Personal Branding untuk Kepercayaan Bisnis sebagai Implementasi SDG’s 5 - Biduri, Sarwenda; Nirwana, Nihlatul Qudus Sukma; Ainindya, Ninik Ruma'isya; Firnata, Tifani Angga (Universitas Muhammadiyah Mataram, 2025)
Abstract: The mentoring program for womenpreneurs in the Aisyiyah Branch Leadership (PRA) Pucang aims to increase business confidence through strengthening social capital and personal branding as a form of implementation of Sustainable Development Goal (SDG's) 5 regarding gender equality. The approach used is Participatory Action Research (PAR) and Community Organizer (CO), with activities in the form of business management training, digital marketing, and simple financial recording assistance. The results showed an increase in participants' understanding in utilizing digital technology, building business networks, and creating a positive business image. Despite challenges such as low digital literacy, the program succeeded in motivating participants to be more professional in managing their businesses and adapting to market dynamics. The impact of the program not only supports the growth of individual businesses but also contributes to the economic strengthening of families and local communities. With this holistic approach, PRA Pucang has succeeded in creating a relevant and sustainable model of women's empowerment.Abstrak: Program pendampingan bagi womenpreneur di Pimpinan Ranting Aisyiyah (PRA) Pucang bertujuan meningkatkan kepercayaan bisnis melalui penguatan modal sosial dan personal branding sebagai bentuk implementasi Tujuan Pembangunan Berkelanjutan (SDG’s) 5 mengenai kesetaraan gender. Pendekatan yang digunakan adalah Participatory Action Research (PAR) dan Community Organizer (CO), dengan kegiatan berupa pelatihan manajemen usaha, pemasaran digital, serta pendampingan pencatatan keuangan sederhana. Hasil pendampingan menunjukkan peningkatan pemahaman peserta dalam memanfaatkan teknologi digital, membangun jejaring bisnis, serta menciptakan citra usaha yang positif. Meski terdapat tantangan seperti rendahnya literasi digital, program ini berhasil memotivasi peserta untuk lebih profesional dalam mengelola usaha dan beradaptasi dengan dinamika pasar. Dampak program tidak hanya mendukung pertumbuhan usaha individu tetapi juga berkontribusi pada penguatan ekonomi keluarga dan komunitas lokal. Dengan pendekatan holistik ini, PRA Pucang berhasil menciptakan model pemberdayaan perempuan yang relevan dan berkelanjutan.